Quantitative Analysis of Macular Inner Retinal Layer Using Swept-Source Optical Coherence Tomography in Patients with Optic Tract Syndrome - Goto, Katsutoshi (J Ophthalmol, 2017)
OBJECTIVE: To evaluate macular inner retinal layers using swept-source optical coherence tomography (SS-OCT) in patients with homonymous hemianopia due to optic tract syndrome (OTS). METHODS: Sixteen eyes of 8 patients with OTS were studied. The macular retinal nerve fiber layer (mRNFL), ganglion cell layer and inner plexiform layer (GCL + IPL), and mRNFL and GCL + IPL (GCC) were measured by SS-OCT (DRI OCT-1 Atlantis®).The scanned area was divided into eight regions and two hemiretinae. Each retinal thickness of the OTS group was compared with that of the 25 control subjects. RESULTS: The GCC thickness in the ipsilateral eyes was significantly reduced in all regions, although predominant thinning of the GCC in the contralateral eyes was found in the nasal region. The GCC + IPL thickness was preferentially reduced at the temporal regions in the ipsilateral eyes and at the nasal regions in the contralateral eyes. The reduction rate of the GCL + IPL thickness was 29.6% at the temporal hemiretina in the ipsilateral eyes and 35.2% at the nasal hemiretina in the contralateral eyes. CONCLUSION: We found preferential loss of the GCC + IPL thickness corresponding to the hemifield defects in each eye. Quantitative analysis by SS-OCT is capable of detecting the characteristic RGC loss due to OTS.